1970
DOI: 10.3329/bmrcb.v34i3.1859
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenic purpura among the children attending at two teaching hospitals

Abstract: The presenting features, diagnostic evaluation, seasonal variation and management performed in 110 children with immune thrombocytopenic purpura (ITP) attending at two tertiary level hospitals were evaluated. A peak incidence of children with ITP was observed during the month of June, July and the first step was found in May and lowest in the month of October to December. Mean initial platelet count was 65.5 x 109/L.  35 patients with ITP did not require any treatment who were kept under observation and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Zeller and colleagues showed that most childhood ITP cases occurred during winter months (11). In another study performed by Hafiz et al (12), childhood ITP was mostly diagnosed during the summer and at least in the winter. The first study was performed in Nordic countries where the climate is characterized by short, cool summers and long, cold winters.…”
Section: Discussionmentioning
confidence: 97%
“…Zeller and colleagues showed that most childhood ITP cases occurred during winter months (11). In another study performed by Hafiz et al (12), childhood ITP was mostly diagnosed during the summer and at least in the winter. The first study was performed in Nordic countries where the climate is characterized by short, cool summers and long, cold winters.…”
Section: Discussionmentioning
confidence: 97%